2018
DOI: 10.1002/anie.201812482
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II)‐Dipicolylamine Coordination Nanotheranostics: Toward Synergistic Nanomedicine by Combined Photo/Gene Therapy

Abstract: We report the rational design of coordination‐driven self‐assembly metal–organic nanostructures for multifunctional nanotheranostics. Zinc(II) coordination‐based nano‐formulations capable of loading indocyanine green (ICG) and therapeutic genes were prepared to achieve a fluorescence/photoacoustic imaging‐guided combination photo/gene therapy strategy. We showed the enhanced theranostic capability of zinc(II)‐dipicolylamine‐assisted assembly of ICG, as well as simultaneous targeted gene delivery in an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…In one instance, cRGD‐installed polymeric micelles incorporated with plasmid DNA (pDNA) encoding anti‐angiogenic proteins (i.e., soluble fms‐like tyrosine kinase‐1) successfully targeted tumor vasculature through cRGD‐integrin (e.g., e v β 3 and α v β 5 ) mediated interactions to effectively suppress tumor growth in pancreatic tumor models 85a. An alternative strategy is to use ligand‐installed nanocarriers for vascular disruption to destroy the tumor vasculature, which starves cancer cells and decreases tumor size . This vascular damage can be further promoted by using external stimuli, such as light, to activate cytotoxic reactions.…”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…In one instance, cRGD‐installed polymeric micelles incorporated with plasmid DNA (pDNA) encoding anti‐angiogenic proteins (i.e., soluble fms‐like tyrosine kinase‐1) successfully targeted tumor vasculature through cRGD‐integrin (e.g., e v β 3 and α v β 5 ) mediated interactions to effectively suppress tumor growth in pancreatic tumor models 85a. An alternative strategy is to use ligand‐installed nanocarriers for vascular disruption to destroy the tumor vasculature, which starves cancer cells and decreases tumor size . This vascular damage can be further promoted by using external stimuli, such as light, to activate cytotoxic reactions.…”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…As shown in Figure C and 1D, the DLS determination showed that the nanoparticles had a mean diameter of about 200 nm with PDI of 0.217 and their zeta potential was −22.0 mV, which favoured the EPR effect. It has been demonstrated that the incorporation of ICG into nanoparticles could improve its stability . So extra experiments were carried out to explore that how the dispersity of ICG molecules incorporated in the MnP/ICG/RAPA/PGA influences photothermal property and absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the incorporation of ICG into nanoparticles could improve its stability. [21,22] So extra experiments were carried out to explore that how the dispersity of ICG molecules incorporated in the MnP/ICG/RAPA/PGA influences photothermal property and absorbance. As shown in Figure 1E, the ICG formulation showed a greater temperature increase than free ICG, which might result from the improved stability.…”
Section: Preparation and Characterization Of Mnp/icg/rapa/pga Npsmentioning
confidence: 99%
“…Recently,v arious nucleic acid nanostructures (NANs), such as spherical nucleic acids (SNAs), [8] DNAnanoparticles, [9] and nucleic acid nanogels [10] have been developed for siRNA delivery,o bviating the need for cationic components.T hese cation-free NANs are incapable of triggering positive-chargeinduced cytotoxicity and plasma protein interaction, and thus represent ap romising new direction for the construction of carriers for siRNAd elivery.Given the complicated pathological mechanism/s of refractory disease,c o-delivery of siRNAi nc onjunction with other drug types may offer complimentary and more potent efficacy, relative to conventional monotherapeutic strategies. [11] However,most siRNAand drug co-delivery systems still utilize ac ationic component to encapsulate siRNAa nd are hence subject to the same cytotoxicity potential. Recently, drug-cored [12] or drug-loaded [13] micellar SNAs,inwhich drugs are anchored or encapsulated inside apolymer core together with anucleic-acid-immobilizing shell, represent apromising approach for siRNAa nd drug co-delivery without cationic materials.D espite these improvements,t hese micellar SNAs nanostructures still have ak ey limitation;t he hydrophobic micellar core only allows loading of hydrophobic small…”
mentioning
confidence: 99%